BDS’ Movement in Ethical Consumption for Maslahah Based on Fatwa MUI No. 83 of 2023 - Muslimah Purnamawati, Anni (Fakultas Syariah IAIN madura, 2024)
BDS' Movement well known in Indonesia as namely Gerakan Boikot, which BDS is acronym of Boycott, Divestment, and Sanction. BDS’ Movement is a humanitarian action carried out by societies to oppose Israel's aggressive attacks on Gaza, Palestine and other humanitarian violations. When November 8th 2023, Indonesia Ulama Council (MUI) that fatwa commission issued confirming that supporting Israel aggression against Palestine is haram. It was published in Fatwa No. 83 of 2023 about the Law on Support for the struggle of Palestinian. This paper aim to address to following question about to analysis the extent to which BDS’ Movement has been carried out in society, the ethical consumption of BDS’ Movement, and the problems based on MUI Fatwa No. 83 of 2023. The research method was carried out using a qualitative descriptive method using data sources such as articles, journals, books, interviews and fatwa studies. The results of this research, first, the largest BDS’ movement was characterized by the boycott of products affiliated with Israel in companies in the manufacturing sectors of consumer goods, food and beverage, and fast food. Second, BDS’ Movement towards ethical consumption makes consumers more wiser, shows consumer’s maturity. The value is consistency being boycotted. Third, regarding maslahah, if boycott is not a solution, however, boycott is part of to show our humanity. Indeed, what is happening in Palestine is a physical problem, so it must be resolved physically as well. Boycott is part of a person's wisdom. If we cannot do everything, don’t leave everything, maa laa yudraku kulluh laa yutraku kulluh. Boycott is a personal as well as human being. If there are individuals who can boycott more than others, then we should not underestimate others.